The conditions of preschool education of children with ASD in short-term groups - Don G.V (Moscow State University of Psychology and Education, 2017)
The actual problems of organization of education of preschool aged children with ASD and conditions for providing them with qualified psychological, educational and correctional-development assistance are being addressed. The goals, objectives and conditions for the education of children in short-term groups are enumerated. The conditions for the implementation of the educational program for preschool children with ASD are considered in detail.